Energetic Factors of a Frequency-Controlled Synchronous Electric Drive - B. I. Firago; S. V. Aleksandrovsky (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2018)
As compared to asynchronous frequency-controlled electric drives, synchronous drives are characterized by lower power losses, rigid mechanical characteristics without speed feedback and by the simplest law of frequency control (when the voltage changes proportionally to the frequency). An analytical study of energy factors (power loss, efficiency, power factor) of frequencycontrolled synchronous motor with electromagnetic ignition and with excitation caused by permanent magnets has been fulfilled. The efficiency of the power converter, in this case (i. e. in the case of the frequency converter), depends on the structure of the converter (single-link or two-link), on the power semiconductor devices being used, on additional elements (i. e. chokes, capacitors, transformers, active resistance, etc.). The efficiency of a synchronous electric motor (which is a cofactor of general efficiency of a controlled synchronous electric drive) is of an interest in the scalar frequency control of the mentioned synchronous motor, since there are almost no publications on this subject. Therefore, the energy conversion efficiency of the synchronous motor, which receives energy from the frequency converter at different frequencies and converts to mechanical energy, has been considered. For the convenience of analytical research, we used the widely used concept of relative frequency as the ratio of the current value of the voltage frequency to the nominal one. It is demonstrated that the maximum efficiency is shifted in the direction of a lower load factor with a decrease in the relative frequency of the motor supply voltage. The method of calculating the energy performance of variable frequency synchronous motor that has been developed is illustrated by the graphs of efficiency and cosj for the engine of the SD3 13-34-6 type of the capacity of 500 kW and of a voltage of 6 kV and for a synchronous motor with permanent magnets of the YGT132S4 type of a capacity of 5.5 kW.